2019
DOI: 10.1088/1742-6596/1321/3/032086
|View full text |Cite
|
Sign up to set email alerts
|

Learning tool development of guided inquiry based to reduce of student’s mistake in resolving question on cell division concept

Abstract: This study aims to produce learning tools using the guided inquiry model which is reasonable to reduce misconception in students’ class XII for solving problems ability on the cell division concept. This development research refers to Borg and Gall development which was modified. The collected data were analyzed qualitatively and quantitatively. Validity data using content validity ratio formula by Lickert Scale. Data of learning feasibility, students’ activities, and student responses conducted on observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
2
1
0
Order By: Relevance
“…So it can be concluded that guided inquiry-based worksheets are effectively used in the learning process and can improve students' scientific literacy. This is in accordance with [14] whose research results show that guided inquiry-based worksheets are used effectively because in limited trials, there is an increase in students' learning outcomes and science literacy scores before and after learning using the inquiry learning model. Overall the pre-test mean score was 21.65 and the post-test mean score was 78.5, resulting in an N-gain score of 0.72.…”
Section: Results Of Lkpd Implementationsupporting
confidence: 88%
See 2 more Smart Citations
“…So it can be concluded that guided inquiry-based worksheets are effectively used in the learning process and can improve students' scientific literacy. This is in accordance with [14] whose research results show that guided inquiry-based worksheets are used effectively because in limited trials, there is an increase in students' learning outcomes and science literacy scores before and after learning using the inquiry learning model. Overall the pre-test mean score was 21.65 and the post-test mean score was 78.5, resulting in an N-gain score of 0.72.…”
Section: Results Of Lkpd Implementationsupporting
confidence: 88%
“…This research aims to produce guided inquiry-based LKPD that is suitable for use to increase the scientific literacy of class X MIA students at SMA Negeri 1 Tigalingga in semester 2 biology material through validity and effectiveness testing. This is in line with the statement by [13] that Student Worksheets Based on Guided Inquiry on Fungi Material for Class And [14] stated that the guided inquiry-based LKPD that was developed was practical and effective, through limited trials showed that the implementation of learning obtained a minimum score of 79, student activities obtained a minimum score of 77, with minimum good criteria; and student learning outcomes based on N-gain calculations obtained a minimum score of 79 with minimum high criteria.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation